ALKBH3-mediated m1A demethylation promotes the malignant progression of acute myeloid leukemia by regulating ferroptosis through the upregulation of ATF4 expression - Xin Liu; Xinghua Pan (Hematology)
To investigate the role of ALKBH3 in acute myeloid leukemia (AML), we constructed an animal model of xenotransplantation of AML. Our study demonstrated that ALKBH3-mediated m1A demethylation inhibits ferroptosis in KG-1 cells by increasing ATF4 expression, thus promoting the development of AML. These findings suggest that reducing ALKBH3 expression may be a potential strategy to mitigate AML progression.ABSTRACT Background: Acute myeloid leukemia (AML) is characterized by the unrestrained proliferation of myeloid cells. Studies have shown that ALKBH3 is upregulated in most tumors, but the role of ALKBH3 in AML remains unclear.Methods: In this study, we investigated the function of ALKBH3 in AML cells (KG-1) by immunofluorescence, ELISA, flow cytometry, HE staining, and Western blotting.Results: Our results revealed that ALKBH3 is upregulated in AML and that the downregulation of ALKBH3 inhibited KG-1 cell proliferation and promoted cell apoptosis; at the same time, ALKBH3 upregulated ATF4 expression through m1A demethylation, and the knockdown of ATF4 resulted in increased ferrous iron content; TFR1, ACSL4, and PTGS2 expression; and ROS and MDA levels, whereas SOD and GSH levels and the expression levels of ATF4, SLC7A11, GPX4, and FTH1 decreased in KG-1 cells, thereby promoting ferroptosis. Mechanistically, ALKBH3-mediated m1A demethylation suppressed ferroptosis in KG-1 cells by increasing ATF4 expression, thereby promoting the development of AML.Conclusions: Our study indicated that reducing the expression of ALKBH3 might be a potential target for improving AML symptoms.